2018
DOI: 10.1111/tpj.13934
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal auxin biosynthesis facilitates rhizobial infection in Lotus japonicus

Abstract: Symbiotic nitrogen fixation in legumes requires nodule organogenesis to be coordinated with infection by rhizobia. The plant hormone auxin influences symbiotic infection, but the precise timing of auxin accumulation and the genetic network governing it remain unclear. We used a Lotus japonicus optimised variant of the DII-based auxin accumulation sensor and identified a rapid accumulation of auxin in the epidermis, specifically in the root hair cells. This auxin accumulation occurs in the infected root hairs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 82 publications
0
58
0
1
Order By: Relevance
“…This suggests that strain MSR2 may have evolved in a close relationship with leguminous plants, and possibly as a natural adjuvant of the nodulation process of rhizobial strains. Strain MSR2 is able to produce increased levels of IAA, and possibly other phytohormones such as cytokinins (discussed below), that significantly impact the nodulation process (Miri et al, 2016;Nadzieja et al, 2018). In addition, strain MSR2 contains ACC deaminase activity, which facilitates the nodulation process of leguminous plants by decreasing inhibitory ethylene levels (Nascimento et al, 2016a;Nascimento et al, 2016b;Tavares et al, 2018;Nascimento et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that strain MSR2 may have evolved in a close relationship with leguminous plants, and possibly as a natural adjuvant of the nodulation process of rhizobial strains. Strain MSR2 is able to produce increased levels of IAA, and possibly other phytohormones such as cytokinins (discussed below), that significantly impact the nodulation process (Miri et al, 2016;Nadzieja et al, 2018). In addition, strain MSR2 contains ACC deaminase activity, which facilitates the nodulation process of leguminous plants by decreasing inhibitory ethylene levels (Nascimento et al, 2016a;Nascimento et al, 2016b;Tavares et al, 2018;Nascimento et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…In legumes, several studies have hypothesised a link between LCO (NF) signalling and auxin homeostasis. For instance, an 8 h LCO treatment induces LjTAR1 and LjGH3 expression in Lotus japonicus root hairs (Nadzieja et al, 2018) and a positive synergistic upregulation of MtTAR2 and MtGH3.1 was observed in M. truncatula roots upon LCO + NAA treatment (Herrbach et al, 2017). LCOs are also reported to inhibit local auxin transport and trigger local auxin accumulation in white clover, as measured by GH3::GUS reporter activity (Mathesius et al, 1998).…”
Section: Conservation Of Lco Effects On Auxin Homeostasis and Root Dementioning
confidence: 99%
“…This suggests that LCO perception in M. truncatula leads to the 'potentiation' of auxin responses, which may in turn be important for symbiosis. In legumes, LCOs are also known to interfere with auxin transport and recent data indicate that LCO perception leads to modification of auxin biosynthesis and content in root hairs that is likely to be involved in the rhizobial infection process (Mathesius et al, 1998;Breakspear et al, 2014;Nadzieja et al, 2018). However, the extent of potentiation of auxin responses by LCOs is not known and the specificity or not of this effect to nodulating plants is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Plant hormones also play an important role in controlling the translocation of microdomains in specific regions of the plasma membrane. Treatment of transgenic soybean roots clearly revealed that GmFWL1 and GmFLOT2 are both translocated at the tip of the root hair cells in response to auxin and salicylic acid [71], hormones regulating nodulation and plant-microbe interactions [72][73][74][75][76]. Conversely, cytokinin inhibits this re-location [71] and the infection of root hair cell by rhizobia [77][78][79][80].…”
Section: Regulation Of the Subcellular Localization Of Fwl/cnr Proteinsmentioning
confidence: 99%